Current Understanding of Gut Microbiota in Mood Disorders: An Update of Human Studies - Huang, Ting-Ting; Lai, Jian-Bo; Du, Yan-Li; Xu, Yi; Ruan, Lie-Min; Hu, Shao-Hua (Frontiers in Genetics, 2019)
Gut microbiota plays an important role in the bidirectional communication between the gut and the central nervous system. Mounting evidences suggest that gut microbiota can influence the brain function via neuroimmune, neuroendocrine pathways and the nervous system. Advances in gene sequencing techniques further facilitate investigating the underlying relationship between gut microbiota and psychiatric disorders. In recent years, researchers have preliminarily explored the gut microbiota in patients with mood disorders. The current review aims to summarize the published human studies of gut microbiota in mood disorders. The findings showed the microbial diversity and taxonomic compositions were significantly changed compared with healthy individuals. Most of these findings revealed that short-chain fatty acids (SCFAs)-producing bacterial genera were decreased, while pro-inflammatory genera and those involved in lipid metabolism were increased in patients with depressive episodes. Interestingly, the abundance of Actinobacteria, Enterobacteriaceae was increased and Faecalibacterium was decreased consistently in patients with either bipolar disorder or major depressive disorder. Some studies further indicated that specific bacteria were associated with clinical characteristics, inflammatory profiles, metabolic markers and pharmacological treatment. These studies present preliminary evidence that the important role of gut microbiota in mood disorders through the brain-gut-microbiota axis, which emerges as a promising target for disease diagnosis and therapeutic interventions in the future.